Bench-to-bedside review: Glucose production from the kidney - Cano, Noël (BioMed Central, 2002)
Data obtained from net organ balance studies of glucose production lead to the classic view according to which glucose homeostasis is mainly ensured by the liver, and renal glucose production only plays a significant role during acidosis and prolonged starvation. Renal glucose release and uptake, as well as the participation of gluconeogenic substrates in renal gluconeogenesis, were recently re-evaluated using systemic and renal arteriovenous balance of substrates in combination with deuterated glucose dilution. Data obtained using these methods lead one to reconsider the magnitude of renal glucose production as well as its role in various physiological and pathological circumstances. These findings now conduce one to consider that renal gluconeogenesis substantially participates in postabsorptive glucose production, and that its role in glucose homeostasis is of first importance.